Mastitis in Chinese Breastfeeding Mothers: A Prospective Cohort Study - Tang, Li; Lee, Andy; Qui, L.; Binns, Colin (Mary Ann Liebert, Inc. Publishers, 2014)
Introduction: Mastitis is a common problem encountered by breastfeeding mothers. This study investigated the incidence and risk factors of lactation mastitis among Chinese women. Subjects and Methods: A prospective cohort study on infant feeding practices was conducted during 2010 and 2011 in Jiangyou, Sichuan Province, China. Poisson regression analysis was performed to determine factors influencing the incidence of mastitis within 6 months postpartum. Results: Of the 670 Chinese mothers who were breastfeeding at discharge, 42 women (6.3%) experienced at least one episode of mastitis during the first 6 months after delivery. The cumulative incidence of mastitis was 10.3%. Mothers with a cracked and sore nipple (incidence rate ratio 2.24; 95% confidence interval 1.38, 3.63) and those who felt stressed (incidence rate ratio 3.15; 95% confidence interval 1.56, 6.37) appeared to sustain more episodes of mastitis. Conclusions: The incidence of lactation mastitis was low among Chinese mothers. To further reduce the risk of mastitis, instructions on the correct positioning of the baby during breastfeeding should be emphasized. Providing new mothers with guidance on how to cope with stress may also prevent the recurrence of the condition.